Penguatan Pengelolaan Usaha Kelompok Wanita Tani melalui Pelatihan Partisipatif untuk Meningkatkan Produktivitas dan Kemandirian Ekonomi di Cilenggang - Sri Sutali Bani; Siti Nurjannah Sanusi; Tri Rumayanto (PADMA, 2025)
Women Farmers Groups (KWT) play a strategic role in supporting agricultural development and improving community welfare, particularly at the family and local community levels. However, KWTs in Cilenggang District still face various obstacles in developing agricultural businesses, including limited technical cultivation knowledge, low farm management skills, and minimal use of simple agricultural technologies. The activity implementation method uses a participatory approach that begins with identifying community needs, followed by training and mentoring. The results of the activity show an increase in knowledge, skills, and changes in farming practices among KWT members. Group members began implementing more effective and planned cultivation techniques, implementing simple farm management, and demonstrating increased awareness of the importance of record-keeping and business planning. Overall, business training for Women Farmers Groups has proven to be an effective approach in increasing agricultural yields and women's economic independence in Cilenggang District.